1994
DOI: 10.1164/ajrccm.149.5.7513593
|View full text |Cite
|
Sign up to set email alerts
|

Circulating adhesion molecules in asthma.

Abstract: There is increasing evidence that leukocyte-endothelial adhesion molecules are important in inflammatory airway disease because of their involvement in the primary steps of entrapment and migration of leukocytes to the site of inflammation. Recently, circulating forms of these adhesion molecules have been described, although their origin, fate, and function are still unknown. We have used an antigen capture ELISA to measure the concentrations of circulating intercellular adhesion molecule-1 (cICAM-1), E-select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
65
3

Year Published

1996
1996
2007
2007

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(73 citation statements)
references
References 7 publications
5
65
3
Order By: Relevance
“…The levels of these factors at the exacerbations caused by URTIs did not differ from those in patients with acute asthma without obvious URTIs. The levels of these factors are consistent with the data as previously described in acute asthma without obvious URTIs (Montefort et al 1994;Yokoyama et al 1995; Niimi et al 1998). These findings, therefore, suggest that virus infection may also produce the factors that induce inflammation and bronchospasm observed in acute asthma caused by other than virus infection.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The levels of these factors at the exacerbations caused by URTIs did not differ from those in patients with acute asthma without obvious URTIs. The levels of these factors are consistent with the data as previously described in acute asthma without obvious URTIs (Montefort et al 1994;Yokoyama et al 1995; Niimi et al 1998). These findings, therefore, suggest that virus infection may also produce the factors that induce inflammation and bronchospasm observed in acute asthma caused by other than virus infection.…”
Section: Discussionsupporting
confidence: 91%
“…Levels of sICAM-1 are reported to increase in the serum and sputum of patients with acute bronchial asthma, bronchopulmonary dysplasia, and other inflammatory and immune disorders (Chihara et al 1994;Montefort et al 1994). Likewise, respiratory viruse infections increase ICAM-1 in airway epithelial cells (Terajima et al 1997;Yamaya 2002) and in vascular endothelial cells (Colden-Stanfield et al 1993).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Potential mediators responsible for leukocyte attachment to endothelium include intercellular adhesion molecule-1 (ICAM-1), interleukin-8 (IL-8), and monocyte chemoattractant protein-1 (MCP-1). It has been reported that ICAM-1, a member of the immunoglobulin superfamily, is required for leukocyte migration into inflamed area (3,6,35) and plays an important role in inflammatory disease, including bronchial asthma, lung injury, and ischemic heart disease (18)(19)(20)(21)(22). IL-8, a CXC chemokine that induces the migration and proliferation of endothelial cells and smooth muscle cells, is a potent angiogenic factor that may play a substantial role in atherosclerosis (4,31).…”
mentioning
confidence: 99%
“…Several studies have demonstrated that CD11/ CD18, E-selectin and ICAM-1 are important determinants in neutrophil trafficking [29±34]. Up-regulation of circulating E-selectin and ICAM-1 is found in the airways of patients with asthma and cystic fibrosis [15,16], where marked airway infiltration by eosinophils or neutrophils occurs. Antibodies against E-selectin and ICAM-1 block neutrophil extravasation in rat lungs [33], and inhibit neutrophil trafficking into the inflamed lungs of a rabbit [34].…”
Section: Discussionmentioning
confidence: 99%